6.26 Wyznacz a wiedząc, że prosta k jest prostopadła do prostej m.
a) k:y= 3x+6, m:y=ax-8
b) k:y= (0,25a-3)x+2, m:y=4x-8
c) k:y= 5+(4-2a)x, m:y=-2/3x+11
d) k:y= -x+3a√5, m:y=(2a-√5)x-19a


Odpowiedź :

Odpowiedź:

[tex]a_{1} *a_{2} =-1\\a_{1} =3\\3*a_{2} =-1\\a_{2} =-\frac{1}{3} \\a =-\frac{1}{3} \\\\a_{1} =4 \\4*a_{2} =-1\\a_{2} =-\frac{1}{4} \\\frac{1}{4} a-3=-\frac{1}{4} \\\frac{1}{4} a=-\frac{1}{4}+3\\\frac{1}{4} a=\frac{11}{4} /*4\\a=11\\\\a_{1} =-\frac{2}{3} \\-\frac{2}{3}*a_{2} =-1\\a_{2} =\frac{3}{2} \\4-2a=\frac{3}{2} \\-2a=\frac{3}{2}-4\\-2a=-\frac{5}{2} /:(-2)\\a=\frac{5}{4} \\\\a_{1} =-1\\-1*a_{2} =-1\\a_{2} =1 \\2a-\sqrt{5} =1 / +\sqrt{5} /:2\\a=\frac{1+\sqrt{5} }{2}[/tex]

Szczegółowe wyjaśnienie:

Odpowiedź:

Szczegółowe wyjaśnienie:

a) k jest prostopadła do m

   3 * m = -1

   [tex]m = -\frac{1}{3}[/tex]

b)  k ⊥ m

    (0,25a - 3) * 4 = -1

    a - 12 = -1

    a = 11

c)  k ⊥ m

    [tex](4 - 2a) * (-\frac{2}{3})=-1\\ 4 - 2a = -1 * (-\frac{3}{2} )\\-2a=\frac{3}{2}-4\\ -2a=-\frac{5}{2}/:(-2)\\ a=\frac{5}{4}[/tex]

d)  k ⊥ m

  -1 * (2a - √5) = -1 /:(-1)

   2a - √5 = 1

   2a = 1 + √5

   [tex]a=\frac{1}{2}+\frac{\sqrt{5} }{2}[/tex]